Girl missing - Gerritsen, Tess (Thorndike, Maine : Center Point Large Print, 2014)
Medical examiner Kat Novak fears that a serial killer is stalking the streets, using a deadly drug to do his dirty work. The police are skeptical. The mayor won't listen. Kat's chief suspect is a prominent citizen. As the death toll rises, Kat races to expose a deadly predator who is close enough to touch her.
"Previously published as Peggy Sue Got Murdered."
Keywords: Medical examiners (Law) -- Fiction; Women pathologists -- Fiction; Large type books; Boston (Mass.) -- Fiction; Romantic suspense fiction